2018
DOI: 10.1108/qram-11-2016-0084
|View full text |Cite
|
Sign up to set email alerts
|

Usefulness of enterprise risk management in two banks

Abstract: Purpose The purpose of this paper is to investigate how the management control system, the bank’s control package, influences opinion about the usefulness of risk measurement (RM) in different control contexts before and after a financial crisis, to understand what influences the usefulness of enterprise risk management (ERM) manifested in RM. Design/methodology/approach The study is based on semi-structured interviews in 2000-2010, with senior bank managers of two international banks (Bank A and Bank B) – b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 64 publications
(139 reference statements)
0
5
0
Order By: Relevance
“…To the best of our knowledge, a detailed literature review on ERM is rare. During the analyzed period, we identified four published reviews on ERM, by Bromiley et al (2015), Wu et al (2015), Tworek (2016), and Liff and Wahlstrom (2018). Among these research works, the review of Bromiley et al (2015) from Long Range Planning journal is the most cited one with 102 citations from Web of Science Core Collection.…”
Section: Introductionmentioning
confidence: 99%
“…To the best of our knowledge, a detailed literature review on ERM is rare. During the analyzed period, we identified four published reviews on ERM, by Bromiley et al (2015), Wu et al (2015), Tworek (2016), and Liff and Wahlstrom (2018). Among these research works, the review of Bromiley et al (2015) from Long Range Planning journal is the most cited one with 102 citations from Web of Science Core Collection.…”
Section: Introductionmentioning
confidence: 99%
“…Lim et al (2017) use empirical evidence to examine the banking sectors' operational dynamics and paradoxical nature of risk management systems. Liff and Wahlstrom (2018), in their study, revealed there are not merely different degrees of risk management usage in their two sample banks; they, in fact, have two diverging trajectories. Given this finding, the significance of the organisational structure and its control packages is vital to find a plausible explanation for senior managers' different experiences about the use of risk management.…”
Section: Prior Literature and Theoretical Frameworkmentioning
confidence: 93%
“…They argue that these findings are in sharp contrast to regulators' recommendations. Liff and Wahlström (2018) observe different trajectories from how banks initially judge risk management to how their judgement develops over time dependent on their management control systems. Particularly, organizational structure and strategic alignment have an impact on the possibility to integrate risk management ideas into the overall organization.…”
Section: Development Of Banks' Risk Culture Over Timementioning
confidence: 99%